Pengembangan Media Pembelajaran Lantai Permainan Elektronika untuk Meningkatkan Kemampuan Berhitung Siswa - Amifatuz Zuhriyah (Atthiflah: Journal of Early Childhood Islamic Education, 2018)
The teacher should better equip himself in utilizing and developing learning media so that the learning atmosphere is more enjoyable without reducing the essence of the subject matter being conveyed. Based on observations when the teacher presents the subjects in class there are several subjects who have difficulty in delivering the material, namely mathematics, the subject of multiplication and division of 2 numbers. This is supported also by the learning media. So that the mindset of students who feel bored, do not like mathematics, and assume that mathematics is a difficult and boring subject will change. Anticipating these obstacles, we need an interesting learning media that can stimulate the imagination and creativity of students, one of which is the learning media "Electronics Game Floor" in mathematics.